Candidate Gender and the Media Attention in the 2015 UK General Election. Issue 2 (6th April 2018) - Murphy, Justin; Rek, Beata
Abstract: Some scholars have argued that lower levels of media attention given to female candidates, relative to male candidates, may contribute to the under-representation of women in politics. Yet, other research suggests female candidates may receive more coverage than male candidates. To advance our understanding of this issue, we introduce and analyse a novel dataset measuring the weekly quantity of newspaper coverage given to 72 different candidates across 34 of the most marginal constituencies in the 2015 UK General Election. The data span 31 local and 6 national newspapers. Statistical analyses and two pairs of quantitatively matched, qualitative comparisons suggest that female candidates received more newspaper coverage than male candidates, even after controlling for several alternative predictors of media attention including party, incumbency and time until election. Our findings have important implications for debates about gender equality in British politics.